2022
DOI: 10.1186/s43045-022-00208-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mindfulness-based intervention on post-traumatic stress symptoms among emergency nursing students

Abstract: Background Clinical training stress may negatively affect nursing students’ academic achievement, clinical performance, learning outcomes, well-being, general health, and quality of life. This study aimed to evaluate the effect of mindfulness-based intervention on post-traumatic stress symptoms among emergency nursing students. This study was conducted at the technical institute of nursing, Zagazig University. Three tools were used in the current study: the sociodemographic data sheet, the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Mindfulness is an important aspect of therapeutic self-care, yet it is not emphasized enough in the nursing profession (Penque, 2019; Weber, 2019). Existing literature shows the benefits of mindfulness-based interventions, as self-care practices, in improving many positive health outcomes in the general population and also among nurses (ElKayal & Metwaly, 2022; Erkin & Şenuzun Aykar, 2021; Kriakous et al, 2019).…”
Section: Mindfulness In Nursingmentioning
confidence: 99%
See 3 more Smart Citations
“…Mindfulness is an important aspect of therapeutic self-care, yet it is not emphasized enough in the nursing profession (Penque, 2019; Weber, 2019). Existing literature shows the benefits of mindfulness-based interventions, as self-care practices, in improving many positive health outcomes in the general population and also among nurses (ElKayal & Metwaly, 2022; Erkin & Şenuzun Aykar, 2021; Kriakous et al, 2019).…”
Section: Mindfulness In Nursingmentioning
confidence: 99%
“…Research studies examining mindfulness-based interventions or practices have found many benefits for nurses in various healthcare settings (Bazarko et al, 2013; Duchemin et al, 2015; Hevezi, 2016; Klein et al, 2020; Lan et al, 2014; Suleiman-Martos et al, 2020). For instance, mindfulness intervention decreased stress, anxiety, and burnout and improved well-being among nurses working in the emergency department (ElKayal & Metwaly, 2022), critical care unit (Lan et al, 2014), and psychiatry (Day & Horton-Deutsch, 2004) and also among nursing students (Erkin & Şenuzun Aykar, 2021). Mindfulness intervention also significantly reduced posttraumatic stress symptoms among emergency nursing students in Egypt (ElKayal & Metwaly, 2022).…”
Section: Mindfulness In Nursingmentioning
confidence: 99%
See 2 more Smart Citations